(1)H NMR Relaxometric Study of Molecular Dynamics in a "de Vries" Liquid Crystal - Gradišek, Anton; Domenici, Valentina; Apih, Tomaž; Novotná, Vladimíra; Sebastião, Pedro J (The journal of physical chemistry. B, 2016)
Liquid crystals that exhibit de Vries smectic A phases are promising materials for new generations of ferroelectric liquid crystal displays and other electro-optical devices. We investigated the molecular dynamic properties of a rod-like de Vries liquid crystal compound, namely the 9HL, a (S)-hexyl lactate derivative, in the whole mesophasic range. This is the first molecular dynamics' investigation on a de Vries phase, and the interest of this system is related to the understanding of the structural and supramolecular organization of de Vries SmA phases, which has been a subject of a broad scientific debate in the last years. Proton NMR spin-lattice relaxation times, T1, were measured in the range 100 MHz to 5 kHz, thus covering a very wide range of motional regimes. (1)H NMR dispersion curves and temperature-dependent relaxation rates were analyzed with a global minimum target fitting approach and the main molecular motions, namely reorientational diffusion, translational self-diffusion, layer undulation, and tilting director fluctuations were fully characterized. The molecular dynamics' behavior observed across the SmA-SmC* phase transitions of 9HL was consistent with the proposed cluster diffuse cone model for the de Vries SmA phase.